Co-precipitation of ferrihydrite and silica from acidic hydrometallurgical solutions and its impact on the paragoethite process - Dyer, Laurence G (Curtin University, 2010)
Ferrihydrite is a common iron oxyhydroxide, produced both naturally and industrially. It is often found in association with silica; an example of this is its occurrence in the Paragoethite process applied in zinc hydrometallurgy for the removal of iron from acidic sulphate solutions. In this process, ferrihydrite is the primary constituent of the precipitation residue, but silica also features heavily and is believed to influence both dewatering and the adsorption of ions from solution.While some information is known regarding the physical interaction of ferrihydrite and silica when they are present as distinct phases, the process by which they simultaneously precipitate remains poorly understood. This thesis details investigations leading to a clearer understanding of this process and provides valuable insights into the factors influencing precipitate behaviour.Ferrihydrite precipitates containing varying proportions of silica were prepared via continuous crystallisation, with the aim of achieving a simplified laboratory-based simulation of the reactions that occur within plant liquors during the Paragoethite process. Multiple anionic environments including sulphate (predominant anion in the Paragoethite process), nitrate (common in natural systems) and chloride were used to monitor the influence of anions on the co-precipitation reaction. Accurate control of the slurry pH and temperature were critical to this simulation, as was maintaining steady-state solution concentrations for iron and silicate. The latter was achieved by continuous addition of iron and silicate, with the corresponding continuous removal of reaction product slurry. Analysis focused on the removed slurry using advanced structural and morphological characterisation of the solid phases formed and quantification of solution species depletion. Reaction conditions were selected to favour the formation of ferrihydrite ensuring it was the dominant phase produced.It was found that the presence of ferrihydrite increased both the rate and extent of silica removed by precipitation from solution. This phenomenon is based on surface adsorption and is hindered by the presence of ions that bind strongly with ferrihydrite. Ions such as sulphate compete with soluble silicate molecules for binding sites on the surface, whereas more weakly bound ions like nitrate do not hinder the process. The level of interference was found to be dependent on available surface area, the affinity for the ion’s adsorption and the concentration of both silicate and the ion in question.Oligomeric and colloidal silica were shown to have a significantly different influence on ferrihydrite to that of monosilicic acid. While the crystallinity of ferrihydrite was seen to decrease when precipitated in the presence of monosilicic acid, no similar effect was observed in the presence of silica in a polymeric state. Although a greater proportion of silica was removed from solution when polymerisation had already progressed to a degree, it still imposed less influence on the product crystallinity. This observation underlines the importance of the adsorption-based process that combines the materials during co-precipitation.X-ray scattering pair distribution function (PDF) analysis of the residue solids was instrumental in displaying correlations between declining ferrihydrite crystallinity and particle size. The data indicated that silicon atoms were not incorporated into the ferrihydrite crystal structure, but by inhibiting the growth of primary particles through surface adsorption, co-precipitated silica produced an apparent decrease in ferrihydrite crystallinity.The analyses presented in this thesis were combined to derive proposed mechanisms of co-precipitate formation based on both the presence of monomeric silica and colloidal particles. When monomeric silica (silicic acid) is present ferrihydrite particles form initially followed closely by the adsorption of silicic acid monomers which restrict further growth. The adsorbed silicic acid molecules condense across the ferrihydrite surface and polymerise outward. Particles aggregate before much, if any, silica polymerisation has occurred, and the silica continues to polymerise of the surface of the aggregates. Where oligomeric or colloidal silica is present ferrihydrite particles are produced; there is little or no immediate silica adsorption and therefore the particles grow uninhibited. During aggregation the silica particles aggregate with the ferrihydrite, being incorporated both within and on the surface of the clusters. The results of this work provide the most detailed description of the reaction mechanism in ferrihydrite/silica co-precipitation, and the most thorough analysis of the structure of co-precipitates thus far reported.